The Safety and Efficacy of Dalbavancin and Active Comparator in Pediatric Patients With Acute Bacterial Skin and Skin Structure Infections. Issue 3 (7th December 2022) - Giorgobiani, Manana; Burroughs, Margaret H.; Antadze, Tinatin; Carrothers, Timothy J.; Riccobene, Todd A.; Patel, Rinal; Lin, Tao; Stefanova, Penka
Abstract : Background: Acute bacterial skin and skin structure infections (ABSSSIs) are a significant source of morbidity in children. Dalbavancin, approved for the treatment of adults and children with ABSSSI, has a well-established safety profile in adults. We report safety and descriptive efficacy data for the treatment of ABSSSI in children. Methods: Children with ABSSSI (birth–<18 years old) or sepsis (<3 months old) known/suspected to be caused by susceptible Gram-positive organisms were enrolled in this phase 3, multicenter, open-label, comparator-controlled study (NCT02814916). Children ≥3 months old were randomized 3:3:1 to receive single-dose dalbavancin, 2-dose dalbavancin, or a comparator antibiotic in 4 age cohorts; those <3 months old received single-dose dalbavancin. Clinical response and microbiologic efficacy were evaluated 48–72 hours and 14, 28 and 54 days posttreatment. Bowel flora testing and audiology were collected in a subset of patients at baseline and day 28. Adverse events (AEs) were collected throughout the study. Results: Treatment-emergent AEs occurred in 7.2%, 9.0% and 3.3% of patients in dalbavancin single-dose, dalbavancin 2-dose and comparator arms, respectively. Three serious AEs occurred in the dalbavancin single-dose arm; no treatment-related AEs, serious AEs, or AEs leading to study discontinuation were reported. Favorable clinical response at 48–72 hours was documented in 97.4%, 98.6% and 89.7% of patients. Safety and efficacy were comparable across age cohorts. The microbiologic intent-to-treat population had comparable clinical response for all baseline pathogens, including methicillin-resistant Staphylococcus aureus . Conclusion: The safety profile of dalbavancin was consistent in children and adults with ABSSSI. No new safety signals were identified.